Do the determinants of non-performing loans have a different effect over time? A conditional correlation approach - Mariagrazia Fallanca; Antonio Fabio Forgione; Edoardo Otranto (Journal of Risk and Financial Management, 2021)
Several studies have explored the linkage between non-performing loans and major macroeconomic indicators, using a wide variety of methodologies, sometimes with different results. This occurs, we argue, because these relationships are generally derived in terms of correlation coefficients evaluated in certain time spans, which represent a sort of average level of correlations. However, such correlations are necessarily time-varying, because the relationships between bank loan indicators and macroeconomic variables could be stronger during particular periods or in correspondence with important economic events. We propose an empirical exercise using dynamic conditional correlation models, with constant and time-varying parameters. Applying these models to quarterly delinquency rates and an array of macroeconomic variables for the US, for the period 1985-2019, we find that the correlation is often negligible in this period except during periods of economic crises, in particular the early 1990 crisis and the subprime mortgage crisis.
Keywords: 330; delinquency rates; macroeconomic factors; Dynamic Conditional Correlation; non-linear autoregressive models